Randomized, controlled trial of a sustained delivery formulation of 5-Fluorouracil for the treatment of failing blebs - Narayanaswamy, Arun Kumar (2013)
Purpose: To determine the efficacy of a subconjunctival injection of hyaluronic acid (HA) with 5-fluorouracil (5FU) formulation as an adjunct in reviving bleb function by needling. Design: Prospective, randomized, controlled trial. Participants: Fifty patients with previous trabeculectomy and scheduled by the managing physician for a needling intervention. Methods: One eye of each patient was randomized to receive needling with HA-5FU mixture or needling with subconjunctival injection of 5FU solution alone. Main Outcome Measures: The primary outcome was the percentage of subjects with an intraocular pressure (IOP) <15 mmHg without any medications at 3 months. Secondary outcomes included the need for additional needling procedures and changes in bleb morphology. Results: Forty-nine subjects (25 in the HA-5FU group and 24 in the 5FU group) completed 3 months of follow-up. At baseline, there was no significant difference between the groups in terms of demographic features, subtype of glaucoma, vertical cup-to-disc ratio, or visual field indices. The mean number of glaucoma medications at baseline was higher in the 5FU group (0.8±1.1 [mean ± standard deviation] vs. 0.2±0.6, P = 0.04). An IOP <15 mmHg without medications was reached in 48.0% of subjects in the HA-5FU group and in 33.3% of subjects in the 5FU group (P = 0.2). At 3 months, both groups demonstrated a significant decrease in IOP from baseline (HA-5FU: decrease of 5.9 mmHg [95% confidence interval, 3.4–8.4]; 5FU: decrease of 6.0 mmHg [95% confidence interval, 3.2–8.2]; P<0.001 for both). Intergroup comparisons for IOP change from baseline was not significant (P = 0.9). However, repeat needling was required more frequently in the 5FU group compared with the HA-5FU group (50.0% vs. 12.0%; P = 0.004). There were no significant differences in the number of reported adverse events, bleb vascularity, or morphology between the 2 groups. Conclusions: Subconjunctival injection of HA-5FU to revive bleb function after bleb needling is as effective as 5FU solution. Fewer repeat needlings were required after treatment with HA-5FU, suggesting that the use of a combined formulation of HA-5FU may improve the overall outcomes of bleb needlings. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.